Perkembangan Pemanfaatan Ruang di Desa Bongkasa Pertiwi Badung Bali Setelah Ditetapkannya sebagai Desa Wisata - Anak Agung Bagus Bayu Anggawirya; Syamsul Alam Paturusi; Ciptadi Trimarianto (Universitas Udayana, 2022)
The use of space in Bongkasa Pertiwi Village, Badung Regency, Bali underwent several changes after the village was designated as a tourist village. The main purpose of this study is to determine the development of space utilization after the village is designated as a tourist village and the factors that influence the use of space itself. This study uses a qualitative method, where data collection is done by means of observation and interviews, and document review. Village spatial mapping was carried out with the help of the Geographic Information System (GIS) and Google Earth. The study showed that the largest proportion of land use was for tourism facilities consisting of tourist attractions and other supporting facilities such as homestays, hotels, and villas. Furthermore, the factors that also affect the use of space in this village are physiographic, economic, regulatory, policy, and institutional factors. This study provides practical guidelines in spatial planning in the development of tourist villages.